Fake news and patient-family-physician interaction in critical care: concepts, beliefs and potential countermeasures - Vitale, Filippo; Misseri, Giovanni; Ingoglia, Giulia; Bonanno, Giuseppe; Gregoretti, Cesare; Giarratano, Antonino; Cortegiani, Andrea (Anestezjologia Intensywna Terapia, 2020)
Fake news has been defined as fabricated information mimicking media content in form but not in organizational process or intent. Science and medicine are deeply affected by this increasing phenomenon. Critical care represents a hot spot for fake news due to the high risk of conflictive communication, the rapid turnaround of clinical news and high prevalence of unpleasant information. Communication with patients’ relatives is one of the hardest aspects. The relationship between physicians and families is pivotal to improve relatives’ comfort, and reduce anxiety and pain. Fake news may undermine this relationship, posing an alternative truth between the critical care physician and relatives, which must be countered without worsening their suffering. The aim of this review is to provide intensivists an overview of concepts, characteristics and risk to better understand the fake news phenomenon and counter its potentially devastating effects.